(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Purpose This study investigated the efficacy of theChromagen lens in CVD subjects, and Evaluate theeffects of using Chromagen Lens with CVD.Methods Color vision tests by ishihara before and after chormagen lens filter to measure theimprovement and the city university 3rd edition color vision test for determine the type of CVD.Results Chromagen lenses improved color vision perception in deutan and protan subjects with theIshihara test.The average of improvement in ishiharaplates by± 60 SD responses after wearing thechromagen lens in all subjects was observed.all the identified CVD subjects reported improved colorvision perception with the chromagen lens.Conclusion The chromagen filter improve general color perception, make colors brighter and clearer,allow shades of color, previously unseen, to be observed and discriminated and improve color naming,improve performance on color vision tests. Can use the chromagen lens in jobsrequire excellent colorperception for example Soldiers, pilots, engineers and designers and use these lenses with goodillumination and after finishing work can be removed.